Dynamics Analysis of the Asynchronous Starting of Converter Tilting Mechanism Reducer based on ADAMS - Ren Xueping; Yang Songtao (Jixie chuandong)
In the process of production of a steel plant of 210 tconverter tilting mechanism,there is a fracture failure of the high speed shafts of reducer.Through the test finding that one of the motors start 0.2slater than others.Aiming at this out-sync phenomenon,the geometry entity model of the reducer which is set up in Pro/E is imported into the software ADAMS.In ADAMS,the dynamics analysis of the model is carried out in the case that the four motors are not starting out of step.The results,a conclusion can be drawn that there is a huge impact between the large gear and a gear shaft of reducer,and uneven loads between four gear shafts.